Burnout syndrome in Industrial Safety Supervisors from Arequipa City - Arias Gallegos, Walter (2014)
burnout syndrome manifestations in a sample of 58 occupational safety supervisors (54.3% male and 46.6% female) with an age range among 22 and 58 years old. The Maslach Burnout Inventory (General Survey) was applied and the results show that 87% percent of supervisors tested have moderate levels of burnout. Moreover, inefficacy reached highest levels of severity of three dimensions of burnout syndrome. Time of service was related to exhaustion and cynicism, meanwhile age was related to inefficacy. Women were more affected by the syndrome comparing to male, but these differences were not significant.